1996
DOI: 10.1046/j.1365-201x.1996.521294000.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid plasma volume decline upon quiet standing reflects large filtration capacity in dependent limbs

Abstract: The plasma volume (PV) decline upon 1.5, 3, 5, 8, 10, 15 and 35 min periods of quiet standing was studied (Hb/Hct) in male volunteers (n = 7). This approach permitted detailed definition of the time-course of the volume change. PV decreased by as much as 8.5 +/- 0.4% (328 +/- 15 mL) after 3 min standing and by no less than 11.7 +/- 0.4% (466 +/- 22 mL) after 5 min. The reduction was 14.3 +/- 0.7, 16.8 +/- 0.8, 17.7 +/- 0.8 and 17.4 +/- 0.9% after 8, 10, 15 and 35 min, or 568 +/- 30, 671 +/- 39, 707 +/- 41 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 16 publications
2
24
1
1
Order By: Relevance
“…Earlier studies estimated that plasma volume decreased about 10-15 % after 20-30 min in the upright position (Waterfield, 1931;Hagan et al 1978;Hinghofer-Szalkay & Moser, 1986). However, Lundvall et al (Lundvall & Bjerkhoel, 1994;Lundvall et al 1996) recently demonstrated that venous blood sampled from the standing subject underestimated the time course and magnitude of reduction in plasma volume. The underestimation was ascribed to incomplete mixing of venous blood from dependent and non-dependent regions.…”
Section: Regulation Of Blood Pressure and Venous Capacitance In Healtmentioning
confidence: 99%
“…Earlier studies estimated that plasma volume decreased about 10-15 % after 20-30 min in the upright position (Waterfield, 1931;Hagan et al 1978;Hinghofer-Szalkay & Moser, 1986). However, Lundvall et al (Lundvall & Bjerkhoel, 1994;Lundvall et al 1996) recently demonstrated that venous blood sampled from the standing subject underestimated the time course and magnitude of reduction in plasma volume. The underestimation was ascribed to incomplete mixing of venous blood from dependent and non-dependent regions.…”
Section: Regulation Of Blood Pressure and Venous Capacitance In Healtmentioning
confidence: 99%
“…19 The filtration coefficient can be chronically altered through exercise or electrical stimulation as well as disease. 20 -22 Our previous work intimated at increased K f in patients with POTS 11,23,24 but stopped short of any definitive statement because of patient heterogeneity, [lack of] subject selection, and technical considerations.…”
Section: Microvascular Filtration Coefficient Is Increased In Potsmentioning
confidence: 99%
“…Independent from the capacitance response, transcapillary fluid filtration is a significant contributor to lower limb volume load and thus important in the orthostatic reaction (10). Accordingly, it has been speculated that an increased capillary filtration during upright posture could affect stroke volume and thus contribute to a progressive fall in cardiac output in orthostatic VVS (66).…”
Section: Effects Of Venous Capacitance and Fluid Filtration On Lbnp Tmentioning
confidence: 99%
“…Previous studies have shown that net fluid filtration into extravascular tissue increases the measured calf volume substantially during VOP, lower body negative pressure (LBNP) and quiet standing (10,30,91,96,110). The effect of net fluid filtration may be especially important to consider because there is compelling evidence that filtration and/or CFC differs among different population groups, e.g., increased net fluid filtration has been shown in patients with postural orthostatic tachycardia syndrome (74) as well as in young women compared to age-matched men (91), whereas reduced net fluid filtration has been seen in aging women (111) and patients with diabetes (76,112).…”
Section: Intravenous Pressure and Correction Of Net Fluid Filtrationmentioning
confidence: 99%
See 1 more Smart Citation